(untitled) (قضايا سياسية, 2024)
The armed conflict in Sudan has not left the history of the state, but what distinguishes this conflict is that it launched a second wave of attempts to split the unity of the state, and perpetuated the absence of a state of political, economic and social stability, in addition to placing the future of the state in a state of open war and chaos from which it may not recover, especially The conflict is the result of a vicious circle between the fragility of the state and the pursuit of power according to the calculations of war, which characterizes the political and military forces involved in the conflict, and this in itself is a scene that revives chaos and leads to its sustainability. What also reinforces this scene is that each party to the conflict did not realize the importance of the state and that the state of war is the human and material destruction of its components, for the simple reason that the state is collapsed from the ground up, as there is no function that it can perform, but rather it is helpless in the face of any attempt to survive, which necessitated The parties seek to pursue the goal of defeating the other militarily, in light of the difficulty of integration in the face of the state of asymmetry between the army on the one hand and the Rapid Support Forces on the other hand, and in light of the absence of national accounts, and the absence of achieving the criteria of victory and defeat in the true sense.